2020
DOI: 10.7717/peerj.8730
|View full text |Cite
|
Sign up to set email alerts
|

Common and specific gene signatures among three different endometriosis subtypes

Abstract: Aims To identify the common and specific molecular mechanisms of three well-defined subtypes of endometriosis (EMs): ovarian endometriosis (OE), peritoneal endometriosis (PE), and deep infiltrating endometriosis (DIE). Methods Four microarray datasets: GSE7305 and GSE7307 for OE, E-MTAB-694 for PE, and GSE25628 for DIE were downloaded from public databases and conducted to compare ectopic lesions (EC) with eutopic endometrium (EU) from EMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Endometriosis is categorized into three subtypes, OE, PE, and DIE. A recent bioinformatic study found that, although there are some common features amongst the different subtypes of endometriosis, PE tended to be more associated with dysregulated peritoneal immune and inflammatory microenvironment while OE and DIE seemed to be at more risk of malignant development [31]. In addition, that report also suggested differences in the lesion microenvironment of three endometriosis subtypes [32].…”
Section: Discussionmentioning
confidence: 98%
“…Endometriosis is categorized into three subtypes, OE, PE, and DIE. A recent bioinformatic study found that, although there are some common features amongst the different subtypes of endometriosis, PE tended to be more associated with dysregulated peritoneal immune and inflammatory microenvironment while OE and DIE seemed to be at more risk of malignant development [31]. In addition, that report also suggested differences in the lesion microenvironment of three endometriosis subtypes [32].…”
Section: Discussionmentioning
confidence: 98%
“…Until now, there have only been a few reports investigating ribonucleotide reductase’s role in endometriosis. One of them is a recent large-scale bioinformatic analysis of previously available microarray datasets, where authors reported RRM2 being downregulated in endometriosis lesions compared to healthy endometrial tissue in the uterus [ 35 ]. Meanwhile they stated that their analysis has limitations by including tissue sample data that were collected from random or unknown menstrual cycle phases.…”
Section: Discussionmentioning
confidence: 99%
“…ESR1 was one of the CDGs and interacted with the hub gene PIK3CA , which was also identified as the hub gene in our study, while other hub genes from our study were not identified as CDGs in Cui's paper. The other excellent paper by Jiang et al integrated four publicly existing microarray datasets including 1 dataset for peritoneal endometriosis (PE), 2 datasets for ovarian endometriosis (OE), and 1 dataset for deep infiltrating endometriosis (DIE) and used the R package limma to identify common and endometriosis subtype-specific DEGs [ 26 ]. Jiang et al found that the PI3K-Akt signaling pathway was significantly enriched for OE-specific DEGs.…”
Section: Discussionmentioning
confidence: 99%